Nitric oxide synthase (NOS3) variants and disease-free survival among treated and untreated breast cancer patients in a SWOG Clinical Trial (S8897) - Choi, Ji-Yeob (2009)
PURPOSE: Numerous chemotherapeutic agents are cytotoxic through generation of reactive species, and variability in genes related to oxidative stress may influence disease free survival (DFS). We examined relationships between DFS and variants in NOS3, as well as NQO1, NQO2 and CBR3 among treated and untreated breast cancer patients in a Southwest Oncology Group clinical trial (S8897). EXPERIMENTAL DESIGN: In the parent trial, women were assigned according to prognostic features; the high risk group was randomized to CMF or CAF ± tamoxifen, and the low risk group did not receive adjuvant therapy. We extracted DNA from normal lymph node tissue and examined functional polymorphisms in NOS3, NQO1, NQO2 and CBR3, in relation to DFS, using Cox proportional hazard model. RESULTS: There were significant interactions between DFS, adjuvant therapy, and NOS3 Glu298Asp and -786 polymorphisms, alone and in combination (p for interaction=0.008). When NOS3 genotypes were combined, women with genotypes encoding for lower NO who received chemotherapy had more than a two fold increase in hazard of progression (HR=2.32, 95% CI=1.26-4.25), while there was reduced risk for those who did not receive adjuvant therapy (HR=0.42, 95% CI=0.19-0.95). There were no associations between the other genotypes and DFS in either group. CONCLUSION: Variants encoding lower activity of NOS3 may affect outcomes in breast cancer patients, with the direction of risk differing depending upon chemotherapy status. These results may mirror the known dual functions of NO and NOS, depending upon oxidative environment.